Occupational stress, work locus of control, masculine ideology, and job satisfaction among male personnel in Lumut Naval Base, Malaysia - Mohd Bokti, Nor Liyana Mohd Bokti (2013)
Job satisfaction is one of the crucial elements in organizational reengineering and it is an important achievement in the adult developmental process including career that dominant by men. The current study was established to determine the relationship between occupational stress, work locus of control, masculine ideology and job satisfaction among male personnel in Lumut Naval Base, Malaysia. A total of 470 respondents were recruited from this main Naval Base in Malaysia using systematic random sampling. The level of occupational stress was measured using Job Related Tension Index by Kahn, et. al (1964), while work locus of control and masculinity ideology were measured using Work Locus of Control Scale (Spector, 1988) and Male Role Norm Inventory-Revised (Lavent, et. al, 1997) respectively. On the other hand, job satisfaction was measured using Job Satisfaction Survey (Spector 1985). Job satisfaction was determined based on nine facets namely pay, promotion, supervision, fringe benefits, contingent rewards, operating procedures, co-workers, nature of work, and communication. Results showed that the majority (63.0%) of Male navy personnel in Lumut Naval Base exhibited ambivalence job satisfaction. Respondents reported least satisfaction with the operating procedures (M = 12.70) and being more satisfied with nature of work (M = 18.04). This study also found a significant relationship between occupational stress and work locus of control on job satisfaction. Besides that, one-way ANOVA analysis found a significant difference of job satisfaction between job classification with Officers being most satisfied as compared to Junior Rank. Finally, multiple regression analysis yielded a multiple coefficient of determination R2 of 0.376 which means that only 37.6% of variation in the job satisfaction was explained by the predictors. Occupational stress was the most significant predictor in determining job satisfaction. Enhancing organizational behaviour and maintaining empowerment of men are unique features of the military that need to be made sense of, interpreted and understood so that the Malaysian Navy can attain world class levels in the future.